Litigation of Sharia Economic Bankruptcy: (Indonesian Bankruptcy Law Perspective) - prihasmoro, adi; Suadi, Amran; Abdullah, Abdul Gani (Jurnal Hukum dan Peradilan, 2025)
This study aims to gain a deep understanding of whether the issue of debts in the scope of sharia economics has been well accommodated in bankruptcy and debt settlement through the Commercial Court based on the Bankruptcy Law. This is normative legal research through literature study and case study, and it is enriched with interviews with sources at the Supreme Court. The results show that there has been an overlap in the court's competency to adjudicate based on applicable laws and regulations. There is no synchronization between the court's competency based on the Bankruptcy Law and based on the Religious Courts Law, especially regarding the settlement of debts within the scope of sharia economics. In the case study on the Commercial Court's decisions, it is known that its final settlements were made without sufficient consideration of sharia economics compliance principles. The Supreme Court, as the holder of judicial power, has attempted to fill the legal vacuum with its policies to synchronize so that the judicial process can run smoothly. Another solution to resolve the overlapping judicial competency arising from the Bankruptcy Law and the Religious Courts Law is to file a judicial review with the Constitutional Court, even though dilemmatic. The remaining issue is that the settlement of debt within the scope of sharia economics is still decided in the Commercial Court, not the Religious Court. The ultimate solution is to propose an amendment to the Bankruptcy Law to accommodate settlements within the scope of sharia economics.